RETRACTION: The Impact of Tourism Development on Economic Condition of Coastal Community in Binyeri Village, Yendidori District, Biak Numfor Regency - Annisa Novita Sari; Ines C. Buiney (ECSOFiM (Economic and Social of Fisheries and Marine Journal), 2020)
RETRACTION TO: Sari, A. N and I.C. Buiney. (2020). The Impact of Tourism Development on Economic Condition of Coastal Community in Binyeri Village, Yendidori District, Biak Numfor Regency. ECSOFiM: Economic and Social of Fisheries and Marine Journal. 08(01): 138-150. http://dx.doi.org/10.21776/ub.ecsofim.2020.008.01.11 . This article has been retracted by the publisher based on the following reason: The editor believes the author violated publication ethics. The author published the same work in two journals. The co-author acknowledges her author's member mis coordinated to submit the same manuscript to another magazine.  This article also has published in the http://www.gjesrm.com/June-2020.html or http://www.gjesrm.com/Issues%20PDF/Archive-2020/June-2020/1.pdf. This journal requires authors to declare that their work is original and has not been published or considered by another journal. This article is a serious scientific publishing misuse. The scientific community strongly disapproves of this, and the journal apologizes to readers for not catching it during submission.